Loss of function of ALDH3B2 transdifferentiates human pancreatic duct cells into β-like cells - Jian Li; Kevin Bode; Yu-chi Lee; Noelle Morrow; Andy Ma; Mulin He; Siying Wei; Jessica da Silva Pereira; Taylor Stewart; Alexander Lee-Papastavros; Jennifer Hollister-Lock; Brooke A. Sullivan; et al. (Science Translational Medicine, 2026)
Replenishment of pancreatic β cells is key to a cure for diabetes. β cell regeneration is achieved predominantly by self-replication, especially in rodents, but it was also shown that pancreatic duct cells can transdifferentiate into β cells. How pancreatic duct cells are transdifferentiated and whether we can manipulate transdifferentiation to replenish β cell mass are not well understood. Using a genome-wide clustered regularly interspaced short palindromic repeats (CRISPR) screen, we found that the loss of function of aldehyde dehydrogenase family 3 member B2 ( ALDH3B2 ) was sufficient to transdifferentiate cell line–based and human pancreatic duct cells into functional β-like cells. The transdifferentiated cells had substantially increased the expression of β cell marker genes, secreted insulin in response to glucose, and lowered blood glucose to near normal for 6 weeks after transplantation into streptozotocin-induced diabetic mice under the kidney capsule. Our study identifies a gene that could potentially be targeted in human pancreatic duct cells to replenish β cell mass for diabetes therapy.